Pengaruh Penentuan Harga dan Kualitas Pelayanan terhadap Minat Pembelian di Muso Art Cafe - Sally Sutresno; Wahyudi Ilham; Rezki Ahmandi; Dailami, Dailami (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
In the era of increasingly intense competition in the food and beverage industry, pricing and service quality have become crucial factors influencing consumers’ purchase intentions. Many food and beverage entrepreneurs compete with competitive pricing and set quality service standards; therefore, this study was conducted to assess whether pricing and service quality at Muso Art Cafe affect consumers’ purchase intentions. This research employs a quantitative approach with an explanatory method, using data collected through questionnaires, interviews, observations, and documentation. The sample consists of 97 respondents selected from Muso Art Cafe customers. Based on the analysis of pricing and service quality toward purchase intention at Muso Art Cafe, the indicators in this study were found to be valid and reliable. The R² value of 0.653 indicates that 66% of purchase intention is influenced by pricing and service quality. The path coefficient test results show that pricing has a significant positive effect with a value of 4.878, meeting the required criterion of >1.96. Similarly, service quality also has a significant positive effect with a value of 2.841, which meets the same criterion of >1.96. Based on these findings, it can be concluded that pricing and service quality both have a significant effect, with pricing being more dominant in influencing purchase intention. This study contributes to the development of consumer behavior theory in the café sector and provides practical implications for culinary business managers in designing effective pricing and service strategies.